OPTIMIZATION OF TRAYEMAN SUB TERMINAL PERFORMANCE IN TEGAL DISTRICT - Agil Suprayogi; Djoko Susilo Adhy (Pondasi, 2018)
The terminal is a public motor vehicle station which used to regulate arrival and departure, pick and drop passenger and/or stuff, and movement of transportation mode. This research aims to know terminal technical performance, quality of service and level of satisfaction and make recommendations for handling to be more optimal.The methods which used in this research for data collection are used terminal inventory survey methods, static surveys and interviews of terminal service users and literary methods. Analysis method using descriptive analysis of terminal technical performance to know the space capacity and terminal facility needs, Importance Performance Analysis (IPA) methods to know perceptions of terminal service users and SWOT analysis methods to obtain optimization strategies for handling. Based on IPA analysis method shows that passenger and driver feel less satisfied with service of sub terminal of Trayeman and obtained SWOT quadrant value for the x-axis is -0.15 and for the y-axis is 1.20 with the recommendations given are change strategy, among others with maintain location, accessibility, stretch path, improvement of main facilities and supporting facilities and with local government fund support in order to improveservice to the community. The calculation of the three investment criteria for structuring the utilization of trayeman sub terminal obtained values NPV Rp.157,692,680 B/C Ratio value is 1.05 and IRR value is 8.23% and it can be concluded that the project is feasible to implement.Key word: Terminal, IPA, SWOT, Investment criteria